2014
DOI: 10.1038/cr.2014.105
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulation: RNF2 targets AMBRA1

Abstract: npgThe phosphatidylinositol 3-kinase complex I (PI3K complex I) is a crucial regulator of autophagy, which contains Beclin 1 (or ATG6), ATG14L, VPS34 (or the class III phosphatidylinositol 3-kinase and its adaptor VPS15) and AMBRA1, and controls autophagosome formation. In a paper recently published in Cell Research, Xia et al. report that during nutrient deprivation the ubiquitin E3 ligase RNF2 is recruited to the PI3K complex I, and ubiquitinates AMBRA1 to trigger its degradation and downregulate autophagy.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…CUL4 can re-associate with AMBRA1 to promote its proteolysis when autophagy terminates, thus regulating autophagy response [ 55 ]. What’s more, E3 ligase RNF2 can also catalyze K48-linked ubiquitination and proteolysis of AMBRA1, thus downregulating autophagy [ 246 ]. Therefore, all the components of the Class III PI3K complex can be regulated by ubiquitination, which exerts important effects on autophagy.…”
Section: Ubiquitination and Autophagymentioning
confidence: 99%
“…CUL4 can re-associate with AMBRA1 to promote its proteolysis when autophagy terminates, thus regulating autophagy response [ 55 ]. What’s more, E3 ligase RNF2 can also catalyze K48-linked ubiquitination and proteolysis of AMBRA1, thus downregulating autophagy [ 246 ]. Therefore, all the components of the Class III PI3K complex can be regulated by ubiquitination, which exerts important effects on autophagy.…”
Section: Ubiquitination and Autophagymentioning
confidence: 99%
“…WASH recruits the RING-type E3 ligase RNF2 ( ring finger protein 2/Ring1b ), which ubiquitinates the residue Lys45 within AMBRA 1 with a Lys48-linked polyubiquitin chain. This modification primes AMBRA 1 for the degradation by the 26S proteasome and finally results in the down-regulation of autophagy [ 75 , 76 ].…”
Section: Regulation Of Beclin 1 Via Distinct Ubiquitination Machinmentioning
confidence: 99%
“…Huang et al indicated that miR-200b inhibits autophagy and triggers apoptosis by directly targeting the autophagy-related gene Ambra1 (autophagy/Be-clin1 regulatory factor 1) [26]. The phosphatidylinositol 3-kinase complex I (PI3K complex I) is a crucial regulator of autophagy, which contains Beclin 1, a long ATG14 isoform of autophagy-related gene 14 (ATG14L), vacuolar protein sorting 34 (VPS34), and Ambra1, and controls autophagosome formation [27].…”
Section: Original Papermentioning
confidence: 99%